Preparation method of high-purity ethylene sulfate
By using titanium silicon molecular sieve catalyst and exchange resin process in the preparation of vinyl sulfate, combined with multi-stage crystallization treatment, the problems of high cost, environmental pollution and low purity in the preparation of vinyl sulfate in the prior art are solved, and high Purity and low-cost vinyl sulfate preparation meet the strict indicators of lithium battery electrolyte.
Patent Information
- Application Number
- CN202411309167.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art has problems such as high cost, environmental pollution, safety risks, inefficient conversion and difficult industrialization in the preparation process of vinyl sulfate, and lithium battery electrolyte has moisture, purity, chloride ions, sulfate ions, and metals of additives. The requirements for ionic and other indicators are high, and the existing purification methods are complex in operation or difficult to achieve high purity.
Titanium silicon molecular sieve TS-1 or modified titanium silicon molecular sieve is used as catalyst, hydrogen peroxide is used as oxidizing agent, and oxidation reaction is carried out in batch kettle type, multi-kettle series continuous type or fixed bed reactor, combining exchange resin and multi-stage crystallization Process, adjust the pH value and cooling rate to achieve the preparation and purification of high-purity vinyl sulfate.
It has achieved efficient, environmentally friendly and low-cost preparation of vinyl sulfate, with a product purity of 99.99%, meeting the strict requirements of lithium battery electrolyte, reducing moisture, chloride ions and metal impurities content, and improving resource utilization and production stability.
Smart Images

Figure CN119192129A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery electrolyte additives, and in particular to a method for preparing high-purity vinyl sulfate. Background Art
[0002] DTD is an additive that can make the electrolyte of lithium-ion batteries more effective. After adding DTD to the electrolyte of lithium-ion batteries, it has the following advantages: ① It can inhibit the decrease of the initial capacity of the battery and increase the initial discharge capacity. ② It can reduce the expansion of the battery after being stored at high temperature, and improve the charge and discharge performance and cycle number of the battery. It can also be used as a hydroxyethylation reagent in organic synthesis to synthesize drug intermediates. It can also be used as a raw material for synthesizing certain heterocyclic compounds for gelatin hardening, antihypertensive drugs and new dual surfactants.
[0003] The structural formula of vinyl sulfite is as follows:
[0004]
[0005] The structural formula of vinyl sulfate is as follows:
[0006]
[0007] The method reported in CN115215834 and CN114210351 is to use vinyl sulfite and sodium hypochlorite as raw materials and ruthenium trichloride as catalyst for oxidation reaction. The catalyst ruthenium trichloride used in this route is expensive and difficult to recycle. Excessive oxidant sodium hypochlorite is used, and the amount of three wastes is large, and a large amount of salt-containing wastewater is produced, which has a great impact on the environment. The sodium and chlorine ion indicators in the product are easy to exceed the standard, increasing the post-processing cost. The method of preparing vinyl sulfate using sulfur trioxide and ethylene oxide in CN106831701 and CN114133375 belongs to gas phase reaction. This method has the disadvantages of high risk in the reaction process, high requirements on equipment, and difficulty in industrial production. CN109776487A discloses a method of using ethylene glycol and sulfonyl chloride as raw materials, chloroform as solvent, and obtaining a crude product of vinyl sulfate through nucleophilic substitution reaction, and then using chloroform crystallization and purification. Although the inconvenient gas raw materials are avoided, the post-processing process is complicated, the amount of wastewater generated is large and difficult to handle, and the environmental pollution is large. CN109422719 uses hydrogen peroxide with a mass concentration of 30% as an oxidant, dichloromethane as a solvent, TS-1 as a catalyst, and the reaction temperature is controlled at 30°C to 40° to synthesize vinyl sulfate in an intermittent reactor. Due to the long reaction time, vinyl sulfate is hydrolyzed in large quantities in the intermittent reactor, and the yield is only 54%. CN116425715 also uses TS-1 as a catalyst, hydrogen peroxide with a mass concentration of 30% as an oxidant, a reaction temperature of 55°C, nitrogen purging, and continuous reaction in a fixed bed. Although a continuous process is adopted, the reaction temperature is high, vinyl sulfate undergoes hydrolysis reaction, the selectivity is not high, and complete conversion is not achieved. The substrate and product need to be separated in the post-processing, and it is difficult to achieve industrialization. At the same time, the lithium battery electrolyte has extremely high requirements on the moisture, purity, chloride ions, sulfate ions, metal ions, acidity and other indicators of the additive. Currently, vinyl sulfate used as an electrolyte additive for lithium batteries is mainly separated and purified by sublimation and solvent recrystallization. The sublimation method has high purity but is complicated to operate and difficult to scale up and industrialize. The solvent method is simple to operate and easy to industrialize, but the organic solvent is difficult to recover and the purity is lower than that of the sublimation method.
[0008] In summary, the existing technologies in the preparation and purification of vinyl sulfate face multiple challenges, such as high cost, environmental pollution, safety risks, low conversion efficiency and difficulty in industrialization. A new technology is urgently needed to solve the above problems. Summary of the invention
[0009] The purpose of the present invention is to overcome the above-mentioned shortcomings and find a green, efficient, catalyst-recyclable, low-byproduct, pollution-free route to synthesize vinyl sulfate. At the same time, a method for preparing high-purity vinyl sulfate by crystallization purification is provided, and the various indicators of the product produced can meet the requirements of lithium battery electrolyte additives. At the same time, the filtrate is applied to improve the crystallization process to solve the problem of organic solvent recovery difficulties in the solvent purification method, achieving the significant advantages of low cost, environmental protection, high yield, high purity and easy industrialization.
[0010] To achieve the above object, the present invention adopts a method for preparing high-purity vinyl sulfate, comprising the following steps:
[0011] (1) Preparation process of vinyl sulfate:
[0012] Using titanium silicalite TS-1 or modified titanium silicalite as a catalyst, 20-80%wt hydrogen peroxide as an oxidant, and an organic solvent as a reaction medium, in an intermittent reactor, a multi-tank series continuous reactor or a fixed bed reactor, a catalytic oxidation reaction is carried out by oxidizing vinyl sulfate, wherein: the molar ratio of vinyl sulfite to the oxidant is 1:1-2.5; the weight ratio of vinyl sulfite to the catalyst is 1:0.02-0.3; the weight ratio of vinyl sulfite to the organic solvent is 1:2-10; the reaction temperature is controlled at 5-60°C, the vinyl sulfate conversion is more than 99%, after the reaction is completed, the reaction solution is separated from the catalyst, the pH value is adjusted to 6-8, the aqueous phase is separated, and the organic solvent is removed under reduced pressure to obtain a crude product of vinyl sulfate;
[0013] (2) Vinyl sulfate purification process:
[0014] The crude product of vinyl sulfate is dissolved in an organic solvent such as an organic ester, ether or halogenated hydrocarbon to obtain a saturated solution, and after alternately using anion and cation exchange resins for adsorption, recrystallization, filtration, washing, and vacuum drying are performed to obtain high-purity vinyl sulfate, with a content of ≥99.95%, moisture ≤20ppm, chloride ion content ≤5ppm, sulfate ion concentration ≤20ppm, acidity ≤20ppm, and total metal impurities ≤10ppm.
[0015] For the technical solution described above, it is further preferred that step (1) uses different reactors:
[0016] The intermittent reactor is a jacketed stirred reactor, the reaction temperature is preferably 10-40°C, the reaction time is 2-5 hours, more preferably 3-5 hours. A single jacketed stirred reactor is used for intermittent operation. The process flow is relatively simple and suitable for small-scale or laboratory preparation.
[0017] The multi-tank series continuous reactor is 2-3 continuous jacketed tank stirring reactors, which are operated in series, and the reaction temperature of each tank is preferably 10-30°C, which can be adjusted independently, and the reaction temperature of each tank can be the same or different, and the total reaction residence time is 2-5 hours, more preferably 2-3 hours. The multi-tank continuous operation can improve the production efficiency and the stability of product quality, and is suitable for medium-scale production.
[0018] The fixed bed reactor is used for continuous flow reaction, the reaction bed temperature is preferably 5-30°C, and the reaction space velocity is 0.2-2h -1 , more preferably 0.5 to 1.2 h -1 Fixed bed reactors have the advantages of high efficiency and ease of large-scale production, providing lower starting temperature options and are suitable for industrial continuous production environments.
[0019] For the technical solution described above, it is further preferred that the reagent for adjusting the pH value in step (1) is selected from at least one of sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate.
[0020] For the technical solution described above, it is further preferred that the organic solvent in step (1) or (2) is one or a mixed solvent of ketones, nitriles, ethers, esters, amides, halogenated hydrocarbons, and aromatic hydrocarbons;
[0021] The ketone solvent described in the present invention is selected from acetone, butanone, and cyclohexanone;
[0022] The nitrile solvent is selected from acetonitrile, propionitrile and butyronitrile;
[0023] The ether solvent is selected from methyl tert-butyl ether, tetrahydrofuran, dipropyl ether, dibutyl ether, and anisole;
[0024] The ester solvent is selected from dimethyl carbonate, diethyl carbonate, ethyl acetate, methyl acetate, methyl acetoacetate, and ethyl acetoacetate;
[0025] The amide solvent is selected from N,N-dimethylformamide, N-methylpyrrolidone, and N-ethylpyrrolidone;
[0026] The halogenated hydrocarbon solvent is selected from chloroform, carbon tetrachloride, trichloroethane, and dichloromethane;
[0027] The aromatic hydrocarbon solvent is selected from benzene, toluene and xylene.
[0028] The most preferred solvent type in the preparation process of vinyl sulfate is ethyl methyl carbonate used in Example 1 or diethyl carbonate used in Example 3;
[0029] The most preferred solvent type in the vinyl sulfate purification process is methylene chloride.
[0030] For the technical solution described above, it is further preferred that the preparation method of the titanium silicon molecular sieve TS-1 catalyst described in step (1) comprises the following steps:
[0031] The template agent tetrapropylammonium hydroxide (TPAOPH) is mixed with deionized water, tetraethyl orthosilicate (TEOS) is added, and stirred to obtain a clear solution; after dissolving n-butyl titanate (TBOT) in isopropanol, it is added dropwise to the above clear solution to obtain a mixture, which is dried, crystallized, and calcined to obtain a TS-1 catalyst.
[0032] The crystallization is performed at 160-170° C. (more preferably 170° C.) for 48-72 hours (more preferably 72 hours);
[0033] The calcination is for template removal and catalyst activation: the temperature is raised to 450-500° C. (preferably 550° C.) at a rate of 6-9° C. / min (8° C. / min) in a muffle furnace, and calcined for 9-12 hours (preferably 10 hours).
[0034] For the technical solution described above, it is further preferred that the molar ratio of the vinyl sulfite to the oxidant in step (1) is 1:1.5-2.0; the weight ratio of the vinyl sulfite to the catalyst is 1:0.1-0.2; and the weight ratio of the vinyl sulfite to the organic solvent is 1:3-6.
[0035] For the technical solution described above, it is further preferred that the modified titanium silicon molecular sieve TS-1 catalyst described in step (1) is a titanium silicon molecular sieve loaded with metal, selected from one of the titanium silicon molecular sieve catalyst TS-1-Co loaded with cobalt, the titanium silicon molecular sieve catalyst TS-1-Ni loaded with nickel, the titanium silicon molecular sieve catalyst TS-1-Fe loaded with iron, and the titanium silicon molecular sieve catalyst TS-1-Cu loaded with nickel. This process ensures that the metal ions are evenly distributed in the titanium silicon molecular sieve TS-1 framework, thereby improving the activity and selectivity of the catalyst.
[0036] For the technical solution described above, it is further preferred that the modified titanium silicon molecular sieve catalyst described in step (1) is prepared by an excess impregnation method, comprising the following steps:
[0037] The preparation method of the TS-1 catalyst loaded with metal (Co, Ni, Fe, Cu, Al) comprises the following steps: placing the titanium silicon molecular sieve TS-1 in an impregnation solution of 0.8-1.5 mol / L respectively, wherein the impregnation solution is selected from one of Co(NO3)2, Ni(NO3)2, Fe2(NO3)3, Cu(NO3)2, and Al2(NO3)3 solutions, drying, calcining and activating; completing the preparation of the metal loaded TS-1 catalyst, and obtaining TS-1-Co, TS-1-Ni, TS-1-Fe, TS-1-Cu, and TS-1-Al respectively. Among them, the most preferred catalyst is the TS-1 catalyst loaded with Cu.
[0038] For the technical solution described above, further preferably, the concentration of the impregnation solution is preferably 1.0 mol / L.
[0039] For the technical solution described above, it is further preferred that the immersion is carried out at 60°C (60-80°C) for 24-36 hours (more preferably 24 hours);
[0040] For the technical solution described above, further preferably, the drying is to drain the excess solution after the impregnation is completed, and then dry at 120-140° C. (more preferably 120° C.) for 12 hours to remove moisture.
[0041] For the technical solution described above, it is further preferred that the calcination activation is performed in a muffle furnace under nitrogen protection at 450-550° C. (more preferably 550° C.) for 4-6 (more preferably 4) hours.
[0042] For the technical solution described above, it is further preferred that in the process for purifying vinyl sulfate in step (2), the dissolution temperature of the crude product is 20 to 50°C.
[0043] For the technical solution described above, it is further preferred that the recrystallization described in step (2) controls the cooling rate to be 5-10°C / h, the cooling crystallization endpoint temperature is 0-5°C, and the temperature is maintained for the crystallization to continue for 1-5h.
[0044] For the technical solution described above, it is further preferred that the vacuum drying temperature in step (2) is 35-50°C, the vacuum degree is -0.01Mpa, and the drying time is 6h.
[0045] For the technical solution described above, it is further preferred that the adsorption material in step (2) is an ion exchange resin. Preferred ion adsorption resins are sulfonic acid cation exchange resins and amine anion exchange resins. The adsorption capacity of sulfonic acid cation exchange resins is 1 to 4 meq / g, and the adsorption capacity of amine cation exchange resins is 3 to 8 meq / g.
[0046] For the technical solution described above, it is further preferred that the adsorption conditions described in step (2) are: adsorption temperature 35-40°C, adsorption time 30-50 min, the amount of adsorbent material added is 2-5wt% of the crude amount of vinyl sulfate added, and the concentration of the adsorbent material in the solvent is 0.8-2.7wt%.
[0047] The beneficial effects are specifically reflected in the following aspects:
[0048] 1. Through resin exchange and multi-stage crystallization treatment, the purity of vinyl sulfate is increased to a maximum of 99.99%. Even after ten cycles of mother liquor, the purity of the final product remains above 99.90%, which is much higher than the product obtained by traditional methods.
[0049] 2. The embodiment shows that the sulfate ion, chloride ion, total metal ion content and water content are greatly reduced, with the lowest values being 11.5 ppm, 2.38 ppm, 2.18 ppm and 11 ppm respectively, which are significantly improved compared with the crude product of 573 ppm, 156 ppm, 137 ppm and 1732 ppm.
[0050] 3. The entire purification process realizes the recycling of mother liquor, and the total yield is as high as 90.8% after ten cycles, which reflects the effective utilization of resources and cost savings.
[0051] 4. The purification process uses 40℃ heating for dissolution and 5℃ crystallization, combined with a controllable cooling rate of 5℃ / h, to avoid the adverse effects of high temperature on the product and ensure the quality and stability of the product.
[0052] 5. The examples show that the method of the present invention has clear operating steps, is easy to control, and maintains good repeatability in multiple cycles, which is conducive to large-scale production and quality control.
[0053] 6. Compared with the traditional purification method in the comparative example, the present invention not only has higher purity, but also has lower ion impurities and water content, which fully demonstrates the superiority of the technical solution. The final product has high purity, meets the strict requirements of lithium battery electrolyte additives, and ensures the reliability and safety of battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 Ethylene sulfate gas phase analysis diagram (Example 3);
[0055] Table 1. Gas phase analysis data of FID1A
[0056] Retention time (min) Compound Name Peak area Peak area (%) 7.513 Ethylene sulfite 0.3 0.01 10.977 Vinyl Sulfate 4201.9 99.99
[0057] The gas phase analysis results of Figure FID1A show that two main compounds can be observed, and the sample is almost entirely composed of vinyl sulfate, with only a very small amount of vinyl sulfite impurity present, which confirms the effectiveness of the preparation method of the present invention and the output of high-purity products. DETAILED DESCRIPTION
[0058] The following embodiments are typical examples for reproducing the present invention and should not be understood as specific limitations on the scheme of the present invention. Therefore, changes made in accordance with the present invention that are merely formal but not substantial are considered to be within the technical content scope of the present invention.
[0059] All titanium silicalite molecular sieves TS-1 used in the following examples were prepared by the following method:
[0060] First, 50.0 g of the template tetrapropylammonium hydroxide (TPAOPH) and 630.0 g of deionized water were completely mixed, and 208.3 g of tetraethyl orthosilicate (TEOS) was added dropwise to the mixture of H2O and TPAOH. After stirring for 1 h, a clear solution was finally obtained. 12.6 g of n-butyl titanate (TBOT) was dissolved in 89.0 g of isopropanol and then added dropwise to the clear solution and stirred for 24 h. Then the mixture was dried at 80 ° C to remove the isopropanol, cooled to room temperature, and transferred to a crystallization kettle. The mixture was crystallized at 170 ° C in an oven under static conditions for 72 h. The obtained mixture was filtered, washed several times with deionized water, and dried. Finally, in order to remove the TPAOPH template, the sample was calcined at 500 ° C in a muffle furnace at a heating rate of 8 ° C / min for 10 h to obtain 51.2 g of TS-1 catalyst.
[0061] The conversion and selectivity of the continuous tank reactor and the fixed bed were calculated by the gas phase external standard method. The standard curves of the substrate vinyl sulfate and the reaction solvent, the product vinyl sulfate and the reaction solvent were prepared.
[0062]
[0063]
[0064] n0(ES): molar amount of vinyl sulfite fed into the fixed bed substrate;
[0065] n1(ES): The molar amount of substrate vinyl sulfite remaining at the end of the reaction.
[0066] Reference standards for metal ions, sulfate ions, chloride ions, acidity, and moisture T / CIESC0042-2022
[0067] Preparation of high purity vinyl sulfate
[0068] Example 1
[0069] Preparation of TS-1-Co catalyst: prepare 1 mol / L Co(NO3)2 solution, weigh 20.0g of calcined TS-1 and add it to a 250ml beaker, add 400ml Co(NO3)2 solution, soak at 60℃ for 24h, after absorption equilibrium, drain the excess solution, dry in an oven at 120℃ for 12h, and calcine at 550℃ for 4h in a muffle furnace under nitrogen atmosphere to obtain the catalyst TS-1-Co catalyst.
[0070] Preparation of vinyl sulfate: 108g (1.0mol) of vinyl sulfite, 500g of ethyl methyl carbonate, and 16.2g of TS-1-Co catalyst were added to a 1000ml intermittent jacketed reactor in sequence, stirred and the system temperature was controlled at 40°C, and then 58.3g of a 70% aqueous hydrogen peroxide solution was added dropwise to the reaction system within 1 hour. After the addition was completed, the mixture was stirred for 2 hours, allowed to stand, and the solid-liquid separation was performed. The mother liquor was adjusted to a pH value of 7.2 with a saturated sodium bicarbonate solution, washed with cold water, dried with 20g of 3A molecular sieves, filtered, and the organic solvent was removed under reduced pressure to obtain 118.8g of a crude product of vinyl sulfate, with a yield of 95.8% and a content of 99.0%.
[0071] Purification of vinyl sulfate: 118.8g of crude vinyl sulfate (purity 99.0%, water content 1456ppm, chloride content 157ppm, sulfate 598ppm, acidity 1267ppm, total metal ion 138ppm) was added to a 500ml jacketed reactor, 373g of dichloromethane was added, and the mixture was heated to dissolve and prepared into a saturated solution. The heating temperature was 35°C. After stirring for 15min, 3g of amino anion resin was added. At 35°C, the mixture was stirred for 30min, filtered, and the mother liquor was poured into another 500ml jacketed reactor. 3g of sulfonic acid cation exchange resin was added to the jacketed reactor. At 35°C, the mixture was stirred for 30min, filtered, and a clear vinyl sulfate solution was obtained. The solution was poured into a 500ml jacketed reactor. Crystallization was performed in the jacketed reactor. The cooling rate was controlled to be 5°C / h. The mixture was stirred slowly. After cooling to 5°C, the temperature was maintained at 5°C and the crystallization was continued for 5h. The crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystal product was washed three times with 20 ml of 5°C dichloromethane, and dried in a vacuum oven at 35°C and -0.01 MPa for 6 h to obtain 78.8 g of pure vinyl sulfate with a yield of 66.3%, a purity of 99.98%, 18 ppm of moisture, 17 ppm of sulfate, 2.9 ppm of chloride ion, 39.3 ppm of acidity, and a total metal ion content of 3.1 ppm. For details, see Table 2.
[0072] Example 2
[0073] Preparation of TS-1-Fe catalyst: prepare 1 mol / L Fe2(NO3)3 solution, weigh 20.0g of calcined TS-1 and add it to a 250ml beaker, add 400ml Fe2(NO3)3 solution, soak at 60℃ for 24h, after absorption equilibrium, drain the excess solution, dry in an oven at 120℃ for 12h, and calcine at 550℃ for 4h in a muffle furnace under nitrogen atmosphere to obtain the catalyst TS-1-Fe catalyst.
[0074] Preparation of vinyl sulfate: 108g (1.0mol) of vinyl sulfite, 500g of ethyl acetate, and 16.2g of TS-1-Fe catalyst were added to a 1000ml intermittent jacketed reactor in sequence, stirred and the system temperature was controlled at 40°C, and then 58.3g of a 70% aqueous hydrogen peroxide solution was added dropwise to the reaction system within 1 hour. After the addition was completed, the mixture was stirred for 4 hours, allowed to stand, and the solid-liquid separation was performed. The mother liquor was adjusted to a pH value of 6.8 with a saturated sodium bicarbonate solution, washed with cold water, dried with 20g of 3A molecular sieves, filtered, and the organic solvent was removed under reduced pressure to obtain 118.9g of a crude product of vinyl sulfate, with a yield of 95.9% and a content of 99.1%.
[0075] Purification of vinyl sulfate: 118.9 g of crude vinyl sulfate (purity 99.1%, water content 1385 ppm, chloride content 146 ppm, sulfate 493 ppm, acidity 1063 ppm, total metal ion 131 ppm) was added to a 500 ml jacketed reactor, 373 g of dichloromethane was added, and the mixture was heated to dissolve and prepared into a saturated solution. The heating temperature was 35 ° C. After stirring for 15 min to completely dissolve, 3 g of amino anion resin was added, and the mixture was stirred at 35 ° C for 30 min, filtered, and the mother liquor was poured into another 500 ml jacketed reactor. 3 g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30 min, filtered to obtain a clear vinyl sulfate solution, and poured into a 500 ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, and the cooling rate was controlled to be 5 ° C / h, and stirring was carried out slowly. After cooling to 5 ° C, the mixture was kept at 5 ° C and stirred for 4 h to complete crystallization. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystal product was washed three times with 20 ml of 5°C dichloromethane, and dried in a vacuum oven at 40°C and -0.01 MPa for 6 h to obtain 77.0 g of pure vinyl sulfate with a yield of 64.8% and a purity of 99.96%. The water content was 11 ppm, the sulfate group was 12 ppm, the chloride ion was 4.27 ppm, the acidity was 28 ppm, and the total metal ion content was 5.44 ppm. For details, see Table 2.
[0076] Example 3
[0077] TS-1-Cu catalyst preparation:
[0078] Prepare 1 mol / L Cu(NO3)2 solution, weigh 20.0g of calcined TS-1 and add it to a 250ml beaker, add 400ml Cu(NO3)2 solution, soak at 60℃ for 24h, after absorption equilibrium, drain the excess solution, dry in an oven at 120℃ for 12h, and calcine at 550℃ for 4h in a muffle furnace under nitrogen atmosphere to obtain the catalyst TS-1-Cu catalyst.
[0079] Preparation of vinyl sulfate: 108g (1.0mol) of vinyl sulfite, 500g of diethyl carbonate, and 16.2g of TS-1-Cu catalyst were added to a 1000ml intermittent jacketed reactor in sequence, stirred and the system temperature was controlled at 40°C, and then 58.3g of a 70% aqueous hydrogen peroxide solution was added dropwise to the reaction system within 1 hour. After the addition was completed, the mixture was stirred for 3 hours, allowed to stand, and the solid-liquid separation was performed. The mother liquor was adjusted to a pH value of 7.1 with a saturated sodium bicarbonate solution, washed with cold water, dried with 20g of 3A molecular sieves, filtered, and the organic solvent was removed under reduced pressure to obtain 119.7g of a crude product of vinyl sulfate, with a yield of 96.5% and a content of 99.5%.
[0080] Purification of vinyl sulfate: Add 119.7g of crude vinyl sulfate (purity 99.5%, water content 1031ppm, chloride content 172ppm, sulfate 493ppm, acidity 962ppm, total metal ion 124ppm) to a 500ml jacketed reactor, add 373g of dichloromethane and heat to dissolve to prepare a saturated solution, the heating temperature is 35°C, stir for 15min to completely dissolve, add 5g of amino anion resin, stir for 30min at 35°C, filter, pour the mother liquor into another 500ml jacketed reactor, add 5g of sulfonic acid cation exchange resin to this jacketed reactor, stir for 30min, filter, obtain a clear vinyl sulfate solution, pour into a 500ml jacketed reactor. Cool down and crystallize in the jacketed reactor, control the cooling rate to 2°C / h, stir slowly, cool to 0°C, keep 0°C and continue crystallization for 3h, and the crystallization is completed. Then, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystals were washed three times with 20 ml of 0°C dichloromethane and dried in a vacuum oven at 35°C and -0.01 MPa for 6 h to obtain 84.75 g of pure vinyl sulfate with a yield of 70.8% and a purity of 99.99%. The content of water was 16 ppm, sulfate was 11 ppm, chloride ion was 4.35 ppm, acidity was 31.8 ppm, and the total metal ion content was 4.3 ppm. See Table 2 for details.
[0081] Example 4
[0082] TS-1-Al catalyst preparation:
[0083] Prepare 1 mol / L Al2(NO3)3 solution, weigh 20.0g of calcined TS-1 and add it to a 250ml beaker, add 400ml Al2(NO3)3 solution, soak at 60℃ for 24h, drain the excess solution after absorption equilibrium, dry in an oven at 120℃ for 12h, and calcine at 550℃ for 4h in a muffle furnace under nitrogen atmosphere to obtain the catalyst TS-1-Al catalyst.
[0084] Vinyl Sulfate Preparation:
[0085] To a 1000ml intermittent jacketed reactor, 108g (1.0mol) of vinyl sulfite, 500g of methyl acetate, and 16.2g of TS-1-Al catalyst were added in sequence, stirred, and the system temperature was controlled at 40°C, and then a 70% mass fraction of hydrogen peroxide aqueous solution was added dropwise to the reaction system within 1 hour. After the addition, the mixture was stirred for 3 hours, allowed to stand, and the solid-liquid separation was performed. The mother liquor was adjusted to a pH value of 7.5 with a saturated sodium bicarbonate solution, washed with cold water, dried with 20g of 3A molecular sieves, filtered, and the organic solvent was removed under reduced pressure to obtain 119.2g of a crude product of vinyl sulfate, with a yield of 96.1% and a content of 99.0%.
[0086] Vinyl Sulfate Purification:
[0087] 119.2g of crude vinyl sulfate (purity 99.0%, water content 1698ppm, chloride content 142ppm, sulfate 534ppm, acidity 1162ppm, total metal ion 126ppm) was added to a 500ml jacketed reactor, 373g of dichloromethane was added, and a saturated solution was prepared by heating at 35°C. After stirring for 15min to completely dissolve, 3g of amino anion resin was added, stirred for 30min, filtered, and the mother liquor was poured into another 500ml jacketed reactor. 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered, and a clear vinyl sulfate solution was obtained, which was poured into a 500ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, and the cooling rate was controlled to be 10°C / h, and stirring was carried out slowly. After cooling to 5°C, crystallization was continued at 5°C for 4h, and crystallization was completed. Then, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dichloromethane and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 61.0 g of pure vinyl sulfate with a yield of 51.2% and a purity of 99.97%. The water content was 13 ppm, the sulfate group was 17 ppm, the chloride ion was 4.76 ppm, the acidity was 36 ppm, and the total metal ion content was 4.03 ppm. For details, see Table 2.
[0088] Example 5
[0089] Preparation of TS-1-Ni catalyst: prepare 1 mol / L Ni(NO3)2 solution, weigh 20.0g of calcined TS-1 and add it to a 250ml beaker, add 400ml Ni(NO3)2 solution, soak at 60℃ for 24h, after absorption equilibrium, drain the excess solution, dry in an oven at 120℃ for 12h, and calcine at 550℃ for 4h in a muffle furnace under nitrogen atmosphere to obtain the catalyst TS-1-Ni catalyst.
[0090] Vinyl Sulfate Preparation:
[0091] To a 1000ml intermittent jacketed reactor, 108g (1.0mol) of vinyl sulfite, 500g of dimethyl carbonate, and 16.2g of TS-1-Ni catalyst were added in sequence, stirred, and the system temperature was controlled at 40°C, and then a 70% mass fraction of hydrogen peroxide aqueous solution was added dropwise to the reaction system within 1 hour. After the addition was completed, the mixture was stirred for 2 hours, allowed to stand, and the solid-liquid separation was performed. The mother liquor was adjusted to a pH value of 7.4 with a saturated sodium bicarbonate solution, washed with cold water, dried with 20g of 3A molecular sieve, filtered, and the organic solvent was removed under reduced pressure to obtain 118.4g of a crude product of vinyl sulfate, with a yield of 95.5% and a content of 99.3%.
[0092] Vinyl Sulfate Purification:
[0093] 118.4g of crude vinyl sulfate (purity 99.3%, water content 1462ppm, chloride ion content 154ppm, sulfate 539ppm, acidity 1069ppm, total metal ion 130ppm) was added to a 500ml jacketed reactor, 120g of dimethyl carbonate was added, and the mixture was heated and dissolved to prepare a saturated solution. The heating temperature was 40°C. After stirring for 15min to completely dissolve, 3g of amino anion resin was added, stirred for 30min, filtered, and the mother liquor was poured into another 500ml jacketed reactor. 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered, and a clear vinyl sulfate solution was obtained, which was poured into a 500ml jacketed reactor. The solution was cooled and crystallized in the jacketed reactor. The cooling rate was controlled to be 5°C / h, and the solution was stirred slowly. After cooling to 5°C, the solution was kept at 5°C for 4h to complete crystallization. The crystallization was completed. Then, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 62.0 g of pure vinyl sulfate with a yield of 52.4% and a purity of 99.95%. The water content was 14 ppm, the sulfate group was 12 ppm, the chloride ion was 3.37 ppm, the acidity was 31 ppm, and the total metal ion content was 4.14 ppm. For details, see Table 2.
[0094] Example 6
[0095] Vinyl Sulfate Preparation:
[0096] In three 500ml continuous jacketed reactors connected in series, each reactor was filled with 10g of TS-1-Cu catalyst, and a 3mol / L dimethyl carbonate solution of vinyl sulfite A and a 50wt% aqueous hydrogen peroxide solution B were prepared. The amount of hydrogen peroxide introduced per unit time was 1.2eq of vinyl sulfite. The reaction temperature was 10°C for the first reactor, 20°C for the second reactor, and 30°C for the third reactor. The total reaction residence time was 2h. The gas phase was sampled and monitored at intervals of 10min. After stabilization, the conversion rate was determined to be 99.4% and the selectivity was 99.2%. 726ml of the outlet solution of the continuous reactor was collected, the mother liquor was adjusted to pH 7.2 with a saturated sodium bicarbonate solution, washed with cold water, dried with 40g of 3A molecular sieve, filtered, and the organic solvent was removed under reduced pressure to obtain 208.0g of crude vinyl sulfate, with a calculated separation yield of 95.8% and a content of 99.7%.
[0097] Vinyl Sulfate Purification:
[0098] 208.0g of crude vinyl sulfate (purity 99.7%, moisture 1433ppm, chloride ion content 147ppm, sulfate 523ppm, acidity 1198ppm, total metal ion 132ppm) was added to a 500ml jacketed reactor, and 200g of dimethyl carbonate was added, and heated to dissolve to prepare a saturated solution, the heating temperature was 40°C, and after stirring for 15min to completely dissolve, 5g of amino anion resin was added, stirred for 30min, filtered, and the mother liquor was poured into another 500ml jacketed reactor, and 5g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered, and a clear vinyl sulfate solution was obtained, which was poured into a 500ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, and the cooling rate was controlled to be 5°C / h, and stirring was carried out slowly. After cooling to 5°C, 5°C was maintained for crystallization for 4h, and crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 111.5 g of pure vinyl sulfate with a yield of 53.6%, a purity of 99.96%, 9 ppm of moisture, 13 ppm of sulfate, 3.72 ppm of chloride ion, 27 ppm of acidity, and a total metal ion content of 5.18 ppm. For details, see Table 2.
[0099] Example 7
[0100] Preparation of vinyl sulfate: In two 500ml continuous jacketed reactors in series, 15g of TS-1-Cu catalyst is added to each reactor, 3mol / L of dimethyl carbonate solution of vinyl sulfite A and 50wt% of hydrogen peroxide aqueous solution B are prepared, and the amount of hydrogen peroxide introduced per unit time is 1.2eq of vinyl sulfite. The reaction temperature is 20°C for the first reactor and 30°C for the second reactor. The total reaction residence time is 2.5h. Continuously introduce, sample the gas phase for monitoring at intervals of 10min, and after stabilization, the conversion rate is determined to be 99.7% and the selectivity is 98.6%. 763ml of the outlet solution of the continuous reactor is collected, the mother liquor is adjusted to pH 7.2 with a saturated sodium bicarbonate solution, washed with cold water, 40g of 3A molecular sieve is added for drying, filtered, and the organic solvent is removed under reduced pressure to obtain 217.0g of crude vinyl sulfate, with a calculated separation yield of 95.1% and a content of 99.3%.
[0101] Purification of vinyl sulfate: Add 217.0g of crude vinyl sulfate (purity 99.3%, moisture 1046ppm, chloride ion content 139ppm, sulfate 329ppm, acidity 709ppm, total metal ion 126ppm) to a 500ml jacketed reactor, add 200g of dimethyl carbonate, heat and dissolve to prepare a saturated solution, the heating temperature is 40°C, stir for 15min to completely dissolve, add 5g of amino anion resin, stir for 30min, filter, pour the mother liquor into another 500ml jacketed reactor, add 5g of sulfonic acid cation exchange resin to this jacketed reactor, stir for 30min, filter, obtain a clear vinyl sulfate solution, pour into a 500ml jacketed reactor. Cool down and crystallize in the jacketed reactor, control the cooling rate to 5°C / h, stir slowly, cool to 5°C, maintain 5°C and continue crystallization for 4h, and the crystallization is completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 123.3 g of pure vinyl sulfate with a yield of 56.8%, a purity of 99.95%, 16 ppm of moisture, 14 ppm of sulfate, 3.04 ppm of chloride ion, 36 ppm of acidity, and a total metal ion content of 5.85 ppm. See Table 2 for details.
[0102] Example 8
[0103] Preparation of vinyl sulfate: TS-1-Cu catalyst was filled in a fixed bed reactor, and a 3 mol / L vinyl sulfite dimethyl carbonate solution A and a 50 wt% hydrogen peroxide aqueous solution B were prepared. The flow rate of solution A was 60 ml / h, the flow rate of solution B was 6.12 ml / h, and the hydrogen peroxide introduced per unit time was 1.2 eq of vinyl sulfite. The reaction temperature was 10°C, the retention time was 62.5 min, and the space velocity was 0.96 h-1 .Continuously pass through, sample the gas phase for monitoring at intervals of 10 minutes, and after stabilization, the conversion rate is 98.5% and the selectivity is 99%. Collect 866 ml of the outlet solution of the fixed bed reactor, adjust the pH value of the mother liquor to 6.7 with a saturated sodium bicarbonate solution, wash with cold water, add 40 g of 3A molecular sieve to dry, filter, and remove the organic solvent under reduced pressure to obtain 249.0 g of crude vinyl sulfate, with a calculated separation yield of 96.2% and a content of 99.5%.
[0104] Purification of vinyl sulfate: Add 249.0g of crude vinyl sulfate (purity 99.5%, water content 786ppm, chloride ion content 157ppm, sulfate 325ppm, acidity 701ppm, total metal ion 135ppm) to a 500ml jacketed reactor, add 240g of dimethyl carbonate, heat and dissolve to prepare a saturated solution, the heating temperature is 40°C, stir for 15min to completely dissolve, add 6g of amino anion resin, stir for 30min, filter, pour the mother liquor into another 500ml jacketed reactor, add 6g of sulfonic acid cation exchange resin to this jacketed reactor, stir for 30min, filter, obtain a clear vinyl sulfate solution, pour into a 500ml jacketed reactor. Cool down and crystallize in the jacketed reactor, control the cooling rate to 5°C / h, stir slowly, cool to 5°C, maintain 5°C and continue crystallization for 4h, and the crystallization is completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C and -0.01 MPa for 6 h to obtain 134.0 g of pure vinyl sulfate with a yield of 53.8% and a purity of 99.97%. The water content was 18 ppm, the sulfate group was 16 ppm, the chloride ion was 3.37 ppm, the acidity was 37 ppm, and the total metal ion content was 6.19 ppm. For details, see Table 2.
[0105] Example 9
[0106] Preparation of vinyl sulfate: TS-1-Cu catalyst was filled in a fixed bed reactor, and a 1 mol / L vinyl sulfite dimethyl carbonate solution A and a 50 wt% hydrogen peroxide aqueous solution B were prepared. The flow rate of solution A was 60 ml / h, the flow rate of solution B was 2.04 ml / h, and the hydrogen peroxide introduced per unit time was 1.2 eq of vinyl sulfite. The reaction temperature was 15°C, the retention time was 40 min, and the space velocity was 1.5 h -1. The gas phase was sampled and monitored at intervals of 10 minutes. After stabilization, the conversion rate was 99.6% and the selectivity was 99.8%. 977 ml of the outlet solution of the fixed bed reactor was collected, and the mother liquor was adjusted to pH 7.0 with a saturated sodium bicarbonate solution, washed with cold water, dried with 40 g of 3A molecular sieve, filtered, and the organic solvent was removed under reduced pressure to obtain 109.0 g of crude vinyl sulfate, with a calculated separation yield of 97.1% and a content of 99.6%.
[0107] Purification of vinyl sulfate: Add 109.0g of crude vinyl sulfate (purity 99.6%, water content 783ppm, chloride ion content 159ppm, sulfate 266ppm, acidity 651ppm, total metal ion 133ppm) to a 500ml jacketed reactor, add 110g of dimethyl carbonate, heat and dissolve to prepare a saturated solution, the heating temperature is 40°C, stir for 15min to completely dissolve, add 3g of amino anion resin, stir for 30min, filter, pour the mother liquor into another 500ml jacketed reactor, add 3g of sulfonic acid cation exchange resin to this jacketed reactor, stir for 30min, filter, obtain a clear vinyl sulfate solution, pour into a 500ml jacketed reactor. Cool down and crystallize in the jacketed reactor, control the cooling rate to 5°C / h, stir slowly, cool to 5°C, maintain 5°C and continue crystallization for 4h, and the crystallization is completed. Then, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 56.2 g of pure vinyl sulfate with a yield of 51.6% and a purity of 99.98%. The water content was 15 ppm, the sulfate group was 18 ppm, the chloride ion was 3.23 ppm, the acidity was 32 ppm, and the total metal ion content was 6.06 ppm. See Table 2 for details.
[0108] Table 3 and Table 4 show the differences between Examples 1-9.
[0109] Table 2 Metal impurity content of vinyl sulfate after purification in each embodiment 1-9 (ppm)
[0110]
[0111]
[0112] Table 3 Differences between the preparation of vinyl sulfate in each example 1-9
[0113] Example catalyst Reactor Reaction temperature / ℃ Solvents Synthesis yield / % purity 1 TS-1-Co Batch kettle 40 Ethyl methyl carbonate 95.8 99.0 2 TS-1-Fe Batch kettle 40 Ethyl acetate 95.9 99.1 3 TS-1-Cu Batch kettle 40 Diethyl carbonate 96.5 99.5 4 TS-1-Al Batch kettle 40 Methyl acetate 96.1 99.0 5 TS-1-Ni Batch kettle 40 Dimethyl carbonate 95.5 99.3 6 TS-1-Cu Continuous Tank 10-20-30 Dimethyl carbonate 95.8 99.7 7 TS-1-Cu Continuous Tank 20-30 Dimethyl carbonate 95.1 99.3 8 TS-1-Cu Fixed bed 10 Dimethyl carbonate 96.2 99.5 9 TS-1-Cu Fixed bed 15 Dimethyl carbonate 97.1 99.6
[0114] By analyzing the data in Table 3, we can see that:
[0115] Example 3: The combination of Cu-loaded TS-1 catalyst and diethyl carbonate as solvent for preparing vinyl sulfate was reacted in an intermittent reactor. Conclusion: The combination of Ni-loaded TS-1 catalyst and diethyl carbonate as solvent showed the highest yield and purity in an intermittent reactor, indicating that this combination has the best effect in an intermittent reactor.
[0116] Example 7: The combination of using Cu-supported TS-1 catalyst and dimethyl carbonate as solvent to prepare vinyl sulfate was reacted in a continuous batch reactor. Conclusion: Compared with the intermittent batch reactor, the reaction temperature was reduced, the reaction time was shortened, and a better yield and purity were obtained.
[0117] Example 9: The combination of Cu-supported TS-1 catalyst and dimethyl carbonate as solvent for preparing vinyl sulfate was reacted in a fixed bed reactor. Conclusion: Compared with Examples 1-7, the reaction time was further shortened, and product decomposition was reduced at a lower temperature, obtaining the highest yield.
[0118] In summary, the best condition parameters are the reaction of Cu-supported TS-1 catalyst with diethyl carbonate as solvent in a fixed bed reactor (Example 9): the highest yield (97.1%) shows that this combination has significant advantages in the preparation of vinyl sulfate.
[0119] Table 4 Differences between the purification of vinyl sulfate in each example of Examples 1-9
[0120]
[0121] Note: The indicators in Table 4 include moisture content, chloride ion content, sulfate content, acidity and total metal ion content, each in ppm (parts per million).
[0122] By analyzing the data in Table 4, we can see that:
[0123] Example 3: Using dichloromethane as solvent and cooling to 0°C at 2°C / h has the highest yield and purity, indicating that this crystallization process has the best effect on the purification of vinyl sulfate.
[0124] Example 10
[0125] Mother liquor was used for the first crystallization: 1. Add 100.0g of crude vinyl sulfate (purity 99.0%, water content 1732ppm, chloride ion content 156ppm, sulfate 573ppm, acidity 1231ppm, total metal ion 137ppm) to a 250ml jacketed reactor, add 102g of dimethyl carbonate, heat and dissolve to prepare a saturated solution, the heating temperature is 40°C, stir for 15min until completely dissolved, add 3g of sulfonic acid cation resin, stir for 30min, filter, pour the mother liquor into another 250ml jacketed reactor, add 3g of amino anion exchange resin to this jacketed reactor, stir for 30min, filter, obtain a clear vinyl sulfate solution, pour into a 250ml jacketed reactor. Cool down and crystallize in the jacketed reactor, control the cooling rate to 5°C / h, stir slowly, cool to 5°C, maintain 5°C and continue crystallization for 4h, and the crystallization is completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The saturated filtrate was heated again to dissolve the crude vinyl sulfate for recycling. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 51.2 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content were determined as shown in Table 5.
[0126] The mother liquor was used for the second crystallization: the filtrate was transferred to a 250ml jacketed reactor, 51.2g of crude vinyl sulfate was added to the jacketed reactor, and the solution was heated to dissolve to prepare a saturated solution. The heating temperature was 40°C. After stirring for 15min to completely dissolve, 3g of amino anion resin was added, stirred for 30min, filtered, and the mother liquor was poured into another 250ml jacketed reactor. 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered, and a clear vinyl sulfate solution was obtained, which was poured into a 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, and the cooling rate was controlled to be 5°C / h. Stirring slowly, after cooling to 5°C, 5°C was maintained for 4h of crystallization, and the crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The saturated filtrate was heated again to dissolve the crude vinyl sulfate for recycling. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 50.1 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content were determined as shown in Table 5.
[0127] The mother liquor was used for the third crystallization: the filtrate was transferred to a 250ml jacketed reactor, 50.1g of crude vinyl sulfate was added to the jacketed reactor, heated and dissolved to prepare a saturated solution, the heating temperature was 40°C, and after stirring for 15min to completely dissolve, 3g of amino anion resin was added, stirred for 30min, filtered, and the mother liquor was poured into another 250ml jacketed reactor, 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered to obtain a clear vinyl sulfate solution, and poured into the 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, the cooling rate was controlled to be 5°C / h, and stirring was carried out slowly. After cooling to 5°C, 5°C was maintained for 4h of crystallization, and the crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The saturated filtrate was heated again to dissolve the crude vinyl sulfate and recycled. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 51.0 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content were determined as shown in Table 5.
[0128] The mother liquor was used for the fourth crystallization: the filtrate was transferred to a 250ml jacketed reactor, 51.0g of crude vinyl sulfate was added to the jacketed reactor, heated and dissolved to prepare a saturated solution, the heating temperature was 40°C, stirred for 15min and completely dissolved, 3g of amino anion resin was added, stirred for 30min, filtered, the mother liquor was poured into another 250ml jacketed reactor, 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered to obtain a clear vinyl sulfate solution, and poured into the 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, the cooling rate was controlled to be 5°C / h, stirring slowly, cooling to 5°C, maintaining 5°C for 4h of crystallization, and the crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The saturated filtrate was heated again to dissolve the crude vinyl sulfate for recycling. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 51.6 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content were determined as shown in Table 5.
[0129] Mother liquor was used for the fifth crystallization: the filtrate was transferred to a 250ml jacketed reactor, 51.6g of crude vinyl sulfate was added to the jacketed reactor, heated and dissolved to prepare a saturated solution, the heating temperature was 40°C, stirred for 15min to completely dissolve, 3g of amino anion resin was added, stirred for 30min, filtered, the mother liquor was poured into another 250ml jacketed reactor, 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered to obtain a clear vinyl sulfate solution, and poured into the 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, the cooling rate was controlled to be 5°C / h, stirring slowly, cooling to 5°C, maintaining 5°C for 4h of crystallization, and the crystallization was completed. After that, the solid-liquid two-phase filtration separation is carried out to obtain vinyl sulfate crystals and a saturated filtrate. The saturated filtrate is heated again to dissolve the crude vinyl sulfate for recycling. The vinyl sulfate crystals are washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 50.8 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content are measured as shown in Table 5.
[0130] The mother liquor was used for the sixth crystallization: the above filtrate was transferred to a 250ml jacketed reactor, 50.8g of crude vinyl sulfate was added to the jacketed reactor, heated and dissolved to prepare a saturated solution, the heating temperature was 40°C, stirred for 15min and completely dissolved, 3g of amino anion resin was added, stirred for 30min, filtered, the mother liquor was poured into another 250ml jacketed reactor, 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered to obtain a clear vinyl sulfate solution, and poured into the 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, the cooling rate was controlled to be 5°C / h, and stirring was carried out slowly. After cooling to 5°C, 5°C was maintained for 4h of crystallization, and the crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The saturated filtrate was heated again to dissolve the crude vinyl sulfate for recycling. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 47.5 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content were determined as shown in Table 5.
[0131] The mother liquor was used for the seventh crystallization: the filtrate was transferred to a 250ml jacketed reactor, 47.5g of crude vinyl sulfate was added to the jacketed reactor, heated and dissolved to prepare a saturated solution, the heating temperature was 40°C, stirred for 15min and completely dissolved, 3g of amino anion resin was added, stirred for 30min, filtered, the mother liquor was poured into another 250ml jacketed reactor, 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered to obtain a clear vinyl sulfate solution, and poured into the 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, the cooling rate was controlled to 5°C / h, and stirring was carried out slowly. After cooling to 5°C, 5°C was maintained for 4h of crystallization, and the crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The saturated filtrate was heated again to dissolve the crude vinyl sulfate for recycling. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 51.5 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content were determined as shown in Table 5.
[0132] The mother liquor was used for the eighth crystallization: the filtrate was transferred to a 250ml jacketed reactor, 51.5g of crude vinyl sulfate was added to the jacketed reactor, heated and dissolved to prepare a saturated solution, the heating temperature was 40°C, stirred for 15min and completely dissolved, 3g of amino anion resin was added, stirred for 30min, filtered, the mother liquor was poured into another 250ml jacketed reactor, 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered to obtain a clear vinyl sulfate solution, and poured into the 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, the cooling rate was controlled to be 5°C / h, stirring slowly, cooling to 5°C, maintaining 5°C and continuing crystallization for 4h, and the crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The saturated filtrate was heated again to dissolve the crude vinyl sulfate for recycling. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 47.2 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content were determined as shown in Table 5.
[0133] The mother liquor was used for the ninth crystallization: the filtrate was transferred to a 250ml jacketed reactor, 47.2g of crude vinyl sulfate was added to the jacketed reactor, heated and dissolved to prepare a saturated solution, the heating temperature was 40°C, stirred for 15min to completely dissolve, 3g of amino anion resin was added, stirred for 30min, filtered, the mother liquor was poured into another 250ml jacketed reactor, 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered to obtain a clear vinyl sulfate solution, and poured into the 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, the cooling rate was controlled to 5°C / h, and stirring was carried out slowly. After cooling to 5°C, 5°C was maintained for 4h of crystallization, and the crystallization was completed. After that, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate. The saturated filtrate was heated again to dissolve the crude vinyl sulfate and recycled. The vinyl sulfate crystals were washed three times with 20 ml of 5°C dimethyl carbonate and dried in a vacuum oven at 40°C, -0.01 MPa for 6 h to obtain 50.3 g of pure vinyl sulfate. The purity, water content, sulfate ion, chloride ion, and total metal ion content were determined as shown in Table 5.
[0134] Mother liquor was used for the tenth crystallization: the filtrate was transferred to a 250ml jacketed reactor, 50.3g of crude vinyl sulfate was added to the jacketed reactor, heated and dissolved to prepare a saturated solution, the heating temperature was 40°C, stirred for 15min and completely dissolved, 3g of amino anion resin was added, stirred for 30min, filtered, the mother liquor was poured into another 250ml jacketed reactor, 3g of sulfonic acid cation exchange resin was added to the jacketed reactor, stirred for 30min, filtered to obtain a clear vinyl sulfate solution, and poured into the 250ml jacketed reactor. Cooling crystallization was carried out in the jacketed reactor, the cooling rate was controlled to be 5°C / h, stirring slowly, cooling to 5°C, maintaining 5°C for 4h, and the crystallization was completed. Afterwards, solid-liquid two-phase filtration separation was performed to obtain vinyl sulfate crystals and saturated filtrate, and the vinyl sulfate crystals were washed three times with 20 ml of 5° C. dimethyl carbonate, and dried in a vacuum oven at 40° C., -0.01 MPa for 6 h to obtain 49.5 g of pure vinyl sulfate; the purity, water content, sulfate ion, chloride ion, and total metal ion content were measured, as shown in Table 5. The total yield of ten mother liquor cycles was 90.8%.
[0135] Table 5 Purity and impurity content of mother liquor after ten cycles of crystallization
[0136]
[0137] From the analysis of the results in Table 5 above, we can see that:
[0138] 1. Despite multiple cycles of mother liquor crystallization, the purity of vinyl sulfate can be maintained at a stable high level, indicating that the method of the present invention has excellent stability and repeatability and is suitable for industrial continuous production.
[0139] 2. With the increase of the number of crystallization cycles, key impurity indicators such as sulfate ion, chloride ion, total metal ion and water content all meet the application requirements, proving the effective removal of impurities by the resin exchange and crystallization purification process.
[0140] 3. By controlling the cooling rate (5°C / h) and maintaining the low temperature (5°C) for crystallization for 4 hours, the full formation of vinyl sulfate crystals is ensured, which is beneficial to the subsequent filtration separation and improves the purification efficiency.
[0141] 4. The dual treatment of sulfonic acid cation resin and amine anion exchange resin significantly reduces the anion and cation impurities in the product and enhances the purification effect.
[0142] 5. The total recovery rate of the mother liquor after ten cycles reached 90.8%, indicating that the method of the present invention not only improves the purity of the product, but also achieves a higher material recovery rate, reduces the production cost and improves the economic benefit.
[0143] 6. The purification process is equally effective for different batches of crude vinyl sulfate, demonstrating the versatility and wide applicability of the method.
[0144] Comparative Example 1
[0145] Preparation of vinyl sulfate: 108g (1.0mol) of vinyl sulfite, 500g of dichloromethane, and 16.2g of TS-1 catalyst were added to a 1000ml intermittent jacketed reactor in sequence, stirred and the system temperature was controlled at 40°C, and then 58.3g of a 70% aqueous hydrogen peroxide solution was added dropwise to the reaction system within 1 hour. After the addition was completed, the mixture was stirred for 16 hours, allowed to stand, and the solid-liquid separation was performed. The mother liquor was adjusted to a pH value of 7.2 with a saturated sodium bicarbonate solution, washed with cold water, dried with 20g of 3A molecular sieves, filtered, and the organic solvent was removed under reduced pressure to obtain 63.3g of a crude product of vinyl sulfate, with a yield of 51.0% and a content of 97.6%.
[0146] Comparative Example 2
[0147] Preparation of vinyl sulfate: 108g (1.0mol) of vinyl sulfite, 500g of dichloromethane, and 16.2g of TS-1 catalyst were added to a 1000ml intermittent jacketed reactor in sequence, stirred and the system temperature was controlled at 40°C, and then 136g of a 30% aqueous hydrogen peroxide solution was added dropwise to the reaction system within 1 hour. After the addition, the mixture was stirred for 24 hours, allowed to stand, and the solid-liquid separation was performed. The mother liquor was adjusted to a pH value of 7.5 with a saturated sodium bicarbonate solution, washed with cold water, dried with 40g of 3A molecular sieves, filtered, and the organic solvent was removed under reduced pressure to obtain 48.8g of a crude product of vinyl sulfate, with a yield of 39.4% and a content of 93.2%.
[0148] Comparative Example 3
[0149] Preparation of vinyl sulfate: TS-1-Cu catalyst was filled in a fixed bed reactor, and a 1 mol / L vinyl sulfite dimethyl carbonate solution A and a 50 wt% hydrogen peroxide aqueous solution B were prepared. The flow rate of solution A was 60 ml / h, the flow rate of solution B was 2.04 ml / h, and the hydrogen peroxide introduced per unit time was 1.2 eq of vinyl sulfite. The reaction temperature was 30°C, the retention time was 40 min, and the space velocity was 1.5 h -1 The gas was continuously introduced and sampled every 10 minutes for monitoring. After stabilization, the conversion rate was 99.9% and the selectivity was 85.8%.
[0150] Comparative Example 4
[0151] Preparation of vinyl sulfate: TS-1 catalyst was filled in a fixed bed reactor, and a 3 mol / L vinyl sulfite dimethyl carbonate solution A and a 50 wt% hydrogen peroxide aqueous solution B were prepared. The flow rate of solution A was 60 ml / h, and the flow rate of solution B was 6.12 ml / h. The hydrogen peroxide introduced per unit time was 1.2 eq of vinyl sulfite. The reaction temperature was 10°C, the retention time was 62.5 min, and the space velocity was 0.96 h-1. The introduction was continued, and the gas phase was sampled at intervals of 10 min for monitoring. After stabilization, the conversion rate was 78.5%, and the selectivity was 98.2%.
[0152] Through the analysis of Comparative Examples 1 and 2, it can be clearly seen that the prior art uses TS-1 and solvent dichloromethane intermittent method to prepare vinyl sulfate, and there are problems such as low efficiency and insufficient purity. Comparative Example 3 shows that in a fixed bed reactor, using TS-1-Cu catalyst, 30°C can achieve good conversion, but it will cause the decomposition of vinyl sulfate. Comparative Example 4 shows that the use of conventional TS-1 catalyst in a fixed bed reactor cannot achieve complete conversion of vinyl sulfite, and the catalyst performance is low. In contrast, the preparation method proposed in the present invention shows significant advantages in terms of yield, product purity, reaction time, simplicity of post-processing and environmental protection, which is a substantial improvement of the prior art, meets the high standard requirements of lithium battery electrolyte additives, and has obvious industrial application prospects and environmentally friendly characteristics.
[0153] The above is only a preferred embodiment of the present invention. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims, and the description and drawings can be used to interpret the content of the claims.
Claims
1. A method for preparing high-purity vinyl sulfate, characterized in that: The steps include: (1) Preparation process of vinyl sulfate: Using titanium silicalite TS-1 or modified titanium silicalite as a catalyst, 20-80%wt hydrogen peroxide as an oxidant, and an organic solvent as a reaction medium, in an intermittent reactor, a multi-tank series continuous reactor or a fixed bed reactor, a catalytic oxidation reaction is carried out by oxidizing vinyl sulfate, wherein: the molar ratio of vinyl sulfite to the oxidant is 1:1-2.5; the weight ratio of vinyl sulfite to the catalyst is 1:0.02-0.3; the weight ratio of vinyl sulfite to the organic solvent is 1:2-10; the reaction temperature is controlled at 5-60°C, after the reaction is completed, the reaction liquid is separated from the catalyst, the pH value is adjusted to 6-8, the aqueous phase is separated, and the organic solvent is removed under reduced pressure to obtain a crude product of vinyl sulfate; (2) Vinyl sulfate purification process: The crude product of vinyl sulfate is dissolved in an organic solvent such as an organic ester, ether or halogenated hydrocarbon to obtain a saturated solution, and after adsorption with anion and cation exchange resins alternately, recrystallization, filtration, washing, and vacuum drying are performed to obtain high-purity vinyl sulfate, with a content of ≥99.95%, moisture ≤20ppm, chloride ion content ≤5ppm, sulfate ion concentration ≤20ppm, acidity ≤20ppm, and total metal impurities ≤10ppm.
2. The method according to claim 1, characterized in that The step (1) uses different reactors: The intermittent reactor is a jacketed stirred reactor, the reaction temperature is 10-40°C, and the reaction time is 2-5 hours; The multi-tank series continuous reactor is 2-3 jacketed tank stirring reactors connected in series, the reaction temperature of each tank is independently selected from 10 to 30°C, and the total reaction residence time is 2 to 5 hours; The reaction bed temperature of the fixed bed reactor is 5-30°C, and the reaction volume space velocity is 0.2-2h -1 .
3. The method according to claim 1, characterized in that The organic solvent in step (1) or (2) is one or a mixed solvent of ketones, nitriles, ethers, esters, amides, halogenated hydrocarbons, and aromatic hydrocarbons; The ketone solvent described in the present invention is selected from acetone, butanone, and cyclohexanone; The nitrile solvent is selected from acetonitrile, propionitrile and butyronitrile; The ether solvent is selected from methyl tert-butyl ether, tetrahydrofuran, dipropyl ether, dibutyl ether, and anisole; The ester solvent is selected from dimethyl carbonate, diethyl carbonate, ethyl acetate, methyl acetate, methyl acetoacetate, and ethyl acetoacetate; The amide solvent is selected from N,N-dimethylformamide, N-methylpyrrolidone, and N-ethylpyrrolidone; The halogenated hydrocarbon solvent is selected from chloroform, carbon tetrachloride, trichloroethane, dichloromethane, and dichloroethane; The aromatic hydrocarbon solvent is selected from benzene, toluene and xylene.
4. The method according to claim 1, characterized in that: The preparation method of the titanium silicon molecular sieve TS-1 catalyst described in step (1) comprises the following steps: The template agent tetrapropylammonium hydroxide is mixed with deionized water, tetraethyl orthosilicate is added, and stirred to obtain a clear solution; n-butyl titanate is dissolved in isopropanol and then added dropwise to the clear solution to obtain a mixture, which is dried, crystallized, and calcined to obtain a TS-1 catalyst.
5. The method according to claim 4, characterized in that The modified titanium silicon molecular sieve TS-1 catalyst is a metal-loaded titanium silicon molecular sieve, selected from one of the cobalt-loaded titanium silicon molecular sieve catalyst TS-1-Co, the nickel-loaded titanium silicon molecular sieve catalyst TS-1-Ni, the iron-loaded titanium silicon molecular sieve catalyst TS-1-Fe, and the nickel-loaded titanium silicon molecular sieve catalyst TS-1-Cu.
6. The method according to claim 5, characterized in that The modified titanium silicon molecular sieve catalyst described in step (1) is prepared by an excess impregnation method, comprising the following steps: placing the titanium silicon molecular sieve TS-1 in an impregnation solution of 0.8-1.5 mol / L, wherein the impregnation solution is selected from one of Co(NO3)2, Ni(NO3)2, Fe2(NO3)3, Cu(NO3)2, and Al2(NO3)3 solutions, drying, calcining and activating the solution.
7. The method according to claim 1, characterized in that The concentration of the impregnation solution is 1.0 mol / L.
8. The method according to claim 1, characterized in that The recrystallization in step (2) is controlled to have a cooling rate of 5 to 10°C / h, a cooling crystallization endpoint temperature of 0 to 5°C, and the temperature is maintained for a crystallization period of 1 to 5 hours.
9. The method according to claim 1, characterized in that: The adsorption materials described in step (2) are sulfonic acid cation exchange resin and amine anion exchange resin; the adsorption capacity of the sulfonic acid cation exchange resin is 1-4 meq / g, and the adsorption capacity of the amine anion exchange resin is 3-8 meq / g.
10. The method according to claim 1, characterized in that The adsorption conditions of step (2) are as follows: adsorption temperature of 35-40° C., adsorption time of 30-50 min, the amount of adsorbent added is 2-5wt% of the crude amount of vinyl sulfate added, and the concentration of the adsorbent in the solvent is 0.8-2.7wt%.
Citation Information
Patent Citations
Method for preparing ethylene sulfate
CN109776487A
Electronic grade citric acid and production method thereof
CN101973871A
Green synthesis method of cyclic sulfate
CN116768848A
Preparation method of ethylene sulfate
CN118496194A